Dosis de compost de bazofia bovina en el rendimiento de Pennisetum sp. Cuba 22 en Loreto, Perú- 2023 - Vargas Linares, Roy Alvaro (2024)
There are many techniques for the management of organic waste and one of those alternatives is compost, as an alternative fertilizer for the fertilization of pastures and forages. The present research is titled: “DOSE OF BOVINE SPOUSE COMPOST IN THE PERFORMANCE OF Penisetum sp. CUBA 22 IN LORETO, PERU- 2023”, with a completely randomized block design with four treatments T0 (control), T1 (10 tons of compost/ha), T2 (20 tons of compost/ha) and T3 (30 tons of compost/ha) and four repetitions, giving the following results, the higher the dose of swill-based compost, the value of the dependent variables of the research increases under the agroclimatic conditions of the area. The plant height (m) was 2.01 m. with T3 (30 tons/ha). In green matter (kg/m2) of 5.3 kg/m2. And dry matter of 1.27 kg/m2 with the T3 treatment (30 tons/ha). The green matter of leaves per square meter of 1.96 and stems of 3.34 kg/m2, with the T3 treatment (30 tons/ha) and the yield of green matter kg/ha of 52.975 kg/ha.